Viviendo en las márgenes del imperio: Luis Jerónimo de Oré y la exploración del Otro - Cook, Noble David (2008)
This essay reconstructs the biography of the Franciscan Luis Jerónimo de Oré, one of the most distinguished personages of American colonial history of the late sixteenth and early seventeenth centuries. It emphasizes his role as missionary in the New World and representative of his order in Europe. Member of a long-honored family of the local elite in Huamanga, Oré established ties with other cultural groups in diverse regions such as the central Andes of Peru and Bolivia, the coast of Florida, and southern Chile.